2020
DOI: 10.3390/biom10111546
|View full text |Cite
|
Sign up to set email alerts
|

Compounds from Natural Sources as Protein Kinase Inhibitors

Abstract: The advantage of natural compounds is their lower number of side-effects when compared to most synthetic substances. Therefore, over the past several decades, the interest in naturally occurring compounds is increasing in the search for new potent drugs. Natural compounds are playing an important role as a starting point when developing new selective compounds against different diseases. Protein kinases play a huge role in several diseases, like cancers, neurodegenerative diseases, microbial infections, or inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 222 publications
1
30
0
Order By: Relevance
“…Certain tyrosine kinase receptors are essential for normal cell regulation and function. However, its dysregulation promotes the growth of tumors and blood vessels via tumor angiogenesis [ 24 , 25 ]. These kinases are generally present as monomers on the cell surface which bind with different growth factors to initiate kinase activities, auto-phosphorylation, and dimerization [ 26 , 27 ].…”
Section: Basic Concept On Targeting Receptor Tyrosine Kinases: Effective Strategies To Cure Cancermentioning
confidence: 99%
“…Certain tyrosine kinase receptors are essential for normal cell regulation and function. However, its dysregulation promotes the growth of tumors and blood vessels via tumor angiogenesis [ 24 , 25 ]. These kinases are generally present as monomers on the cell surface which bind with different growth factors to initiate kinase activities, auto-phosphorylation, and dimerization [ 26 , 27 ].…”
Section: Basic Concept On Targeting Receptor Tyrosine Kinases: Effective Strategies To Cure Cancermentioning
confidence: 99%
“…Kinases play a significant role in tumorigenesis, cancer cells’ survival, and proliferation. Different studies on human kinases were able to report 555 types of protein kinases based on their sequence analysis and evolutionary history ( Baier and Szyszka, 2020 ). Out of this, 497 were grouped into eukaryotic protein kinases and 58 as atypical kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol serves as a chemopreventive agent 18,19 and displays chemotherapeutic properties that are attributed to its antioxidant, anti‐inflammatory, proapoptotic, and antiproliferative features 17,20 . Resveratrol is supposed to target intracellular signalling pathway components including regulators of cell survival and apoptosis, pro‐inflammatory mediators, and key components of tumour angiogenesis and metastasis by interfering with a distinct set of transcription factors, upstream kinases, and their regulators 21–23 …”
Section: Introductionmentioning
confidence: 99%
“…17,20 Resveratrol is supposed to target intracellular signalling pathway components including regulators of cell survival and apoptosis, proinflammatory mediators, and key components of tumour angiogenesis and metastasis by interfering with a distinct set of transcription factors, upstream kinases, and their regulators. [21][22][23] In vivo studies demonstrated that resveratrol additionally exerted beneficial effects on metabolic syndromerelated alterations, for example, glucose and lipid homeostasis improvement and a reduction in fat mass, blood pressure, low-grade inflammation, and oxidative stress. [24][25][26][27][28] Further studies verified that resveratrol mimics caloric restriction via the activation of sirtuin 1 (SIRT 1) 26,29 resulting in improved exercise performance and insulin sensitivity, as well as showing body fatlowering effects by inhibiting adipogenesis, and increasing lipid mobilisation in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%